FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK DETEKSI DINI IBU HAMIL RISIKO TINGGI OLEH BIDAN DI KABUPATEN NGANJUK - Titin Ratnaningsih; Remita Yuli Kusumaningrum; Ike Nurrochmawati (JURNAL SABHANGA, 2023)
Maternal Mortality in Nganjuk still high, one of the causes of maternal death iscomplications of pregnancy, maternal mortality reduction efforts is to detect complications as early aspossible so that it will soon acquire an effective referral service. Coverage of early detection of highrisk pregnant women by midwives in Nganjuk District in 2022 was still 11.6% below the MinimumService Standards, for the research was conducted, to determine factors associated with earlydetection of high risk pregnant women by midwives in the District Nganjuk 2023